Between the Past and the Possible: Bugis Identity in Motion - Wahyuddin, Wahyuddin (Humaniora, 2025)
This study explores how the Bugis emerged as a distinct ethnic group by examining the historical, cultural, and social processes that shaped their collective identities. It further investigates the defining features of Bugis’ identity and how ethnic boundaries are constructed, maintained, and negotiated over time. The research were conducted inBugis diaspora areas in Pagatan, South Kalimantan and Jakarta, as well as in several Bugis regions in South Sulawesi—namely Barru, Pangkep, and Bulukumba Regencies—between April and September 2021. This study demonstrates that Bugis’s development as an ethnic group was exclusively connected to the Cina Kingdom in Sulawesi. The expansion of this local kingdom contributed to the formation and shaping ofthe Bugis identity in the ancient period. However, Bugis identity developed and transformed over time; from the tradition of La Galigo it became a Muslim society. In addition, migration and commercial culture helped construct their identity. Re-examining ethnic identity from a long-term historical perspective is important in order to move beyond cultural essentialism, which tends to ignore the shifts and changes as a result from cross-cultural encounters. Ethnic boundaries are not immutable, but are contextually deployed and relationally defined